The impact of using "ISBAR" standard checklist on nursing clinical handoff in coronary care units - Behrouz Pakcheshm; Imane Bagheri; Zohreh Kalani (Tehran University of Medical Sciences, 2020)
Background and Objective: Clinical handoff is the process of transmitting information, responsibility and accountability among the health care team members. Lack of standard protocols may result in the loss of essential information and also may lead to medical errors. The purpose of this study was to evaluate the impact of using a  standard checklists on clinical handoff in coronary care unit (CCU). Method: This quasi-experimental study was performed based on pre- and post-test design at Afshar Hospital in Yazd. There were a total of 564 handoffs with the participation of 24 nurses in two coronary care units in 2017. Prior to the intervention, 282 clinical handoffs were recorded and implemented. Nurses were informed about the ISBAR standard checklist and were encouraged to use it for one week. Then, 282 clinical handoffs were again recorded and implemented. Frequency of providing information during clinical handoff was determined based on ISBAR checklist and the data were analyzed using descriptive statistics and chi-square test. Results: Prior to the intervention, frequency of providing information during clinical handoff was reported as follows: patient identity (86.9%), current position (75.1%), clinical history (52.8%), system status review (59.9%), and recommendations (92.9%). The results showed that the indexes significantly increased (P <0.001) after the intervention in all these five domains: patient identity (100%), current situation (94%), clinical history (80.1%), system status review (92.2%) and recommendations (100%). Conclusion: Transition of information based on standard checklists with a specific framework can increase the frequency of information provided during clinical handoff. Therefore, it is recommended to train nurses and nursing  students about standard handoff and related tools such as ISBAR in hospitals and universities.